SYNCHRONIZATION OF TWO HOMOGENEOUS DATABASES USING DBFORGE - Arif Setia Sandi A (University of Muhammadiyah Tangerang, 2021)
Database synchronization is part of replication, which is a process to ensure that every copy of data in a database contains similar objects and data. The creation of a database with MySQL database management is made offline and due to the limited allocation of costs to the system. Database synchronization in time and cost is affordable to synchronize the database offline. The main purpose of database optimization is to make many users can access data simultaneously. Accessing this data is not problematic if all users only read data and they do not interfere with each other. But when many users access the same database simultaneously and one makes changes to the data, it can lead to inconsistency of data. From the development objectives, it can be concluded that the importance of synchronizing data to backup databases to maintain consistency. This research was conducted for database optimization using dbForge Schema Compare for MySQL. This research aims to optimize the database with a target market in organizations that have a small cost allocation. Database optimization is expected to contribute to help improve database management functionality, especially offline database management and organizations that have little cost allocation.